ASEG Extended Abstracts 2012 - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (CSIRO, 2012)
A study of the pore fluid effects on the elastic and anelastic properties of sedimentary rocks is important for interpreting seismic data obtained for reservoirs as well as for monitoring the fluid movement during both fluid extraction in producing fields and injection of CO2 for storage purposes. In most sedimentary rocks low intrinsic permeability and, as a consequence, low fluid mobility lead to a situation when relative motion between pore fluid and rock skeleton has significant influence on acoustic wave propagation even at seismic frequencies. Therefore, in many cases the experiments conducted only at seismic frequencies are not sufficient to validate commonly used theoretic models of elastic moduli dispersion and attenuation. We present data obtained with a new version of low-frequency laboratory apparatus designed for measurements of Young’s moduli and extensional attenuation of rocks at seismic (1-400 Hz) and teleseismic (≤1Hz) wave frequencies. The apparatus can operate at confining pressures from 0 to 70 MPa. Elastic and anelastic parameters of dry and water-saturated sandstone quarried in Donnybrook, Western Australia, were measured at various confining pressures and room temperature (~20° C). A peak of attenuation in a water-saturated sample with 14.8% porosity and 7.8 mD permeability was found at frequency 0.8 Hz.